Singapore’s Housing Policies: Responding to the Challenges of Economic Transitions - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2015)
Singapore has developed its own unique state-driven housing system, with more than three quarters of its housing stock built by the Housing and Development Board and homeownership financed through Central Provident Fund savings. As a result, it has one of the highest homeownership rates amongst market economies. This paper provides a historical perspective of the main housing problems faced by successive prime ministers and their respective policy responses. Under the leadership of Prime Minister Lee Kuan Yew (1959-1990), the government established an integrated landhousing supply and housing finance framework to channel much needed resources into the housing sector to deal with a chronic housing shortage. Under Prime Minister Goh Chok Tong (1990-2004), asset enhancement schemes to renew aging estates as well as market deregulation measures were implemented. Prime Minister Lee Hsien Loong (2004-present) has been confronted with a different set of challenges - investment demand for housing, rising inequalities and rapidly aging population. These problems have brought about the introduction of carefully crafted macroprudential policies, targeted housing grants to assist low and middle income households, and schemes to help elderly households monetize their housing equity.